2022
DOI: 10.3389/fmicb.2022.951507
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in gut microbiota of semiprovisioned rhesus macaques (Macaca mulatta) living in a limestone forest of Guangxi, China

Abstract: Assessment of gut microbiota, used to explore ecological adaptation strategies and evolutionary potential of species, provides a new viewpoint to the conservation and management of endangered animals. In this research, the gut microbiota of a group of semiprovisioned rhesus macaques (Macaca mulatta) living in a limestone forest exhibiting seasonal changes in plant items were studied to investigate the adaptation strategies of these macaques to this specific habitat. The findings revealed significant seasonal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 61 publications
(163 reference statements)
1
10
0
Order By: Relevance
“…These plants are eaten by the langurs exclusively in the rainy season, resulting in greater dietary and gut microbiota diversities (Zhou et al, 2013). Similar findings have been reported for rhesus macaques (Liu et al, 2022). Beta diversity analysis indicated significant differences in the gut microbiota of white-headed black langurs across seasons.…”
Section: Seasonal Variationssupporting
confidence: 71%
See 2 more Smart Citations
“…These plants are eaten by the langurs exclusively in the rainy season, resulting in greater dietary and gut microbiota diversities (Zhou et al, 2013). Similar findings have been reported for rhesus macaques (Liu et al, 2022). Beta diversity analysis indicated significant differences in the gut microbiota of white-headed black langurs across seasons.…”
Section: Seasonal Variationssupporting
confidence: 71%
“…Proteobacteria, although reportedly potentially pathogenic, include Succinivibrio, which consumes cellulose and hemicellulose to produce SCFAs (Baniel et al, 2021). These dominant phyla perform major digestive and metabolic functions in the gut, and the taxa with a low proportion maintain the ecological balance of the community and high functional redundancy (Cho and Blaser, 2012;Liu et al, 2022). The F/B (Firmicutes/Bacteroidetes) ratio has been considered an appropriate proxy for energy balance (Turnbaugh et al, 2006;Springer et al, 2017).…”
Section: Composition Of Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…We find that precipitation explains a fraction of the total variation in gut microbiome between individuals. Precipitation influences gut microbiome across various animal hosts (Orkin et al, 2018; Li et al, 2020; Baniel et al, 2021; Liu et al, 2022; Murillo, Schneider, Fichtel, et al, 2022). The putative pathways with which precipitation can influence gut microbiome are 1.…”
Section: Discussionmentioning
confidence: 99%
“…However, this assembly in subtropical rivers is shaped by stochastic processes because the water is more complex and changeable ( Chen et al, 2019 ). In contrast, a study on rhesus macaques with different foods in altered seasons confirmed the dominant role of deterministic processes in microbiota assembly owing to environmental filtering ( Liu et al, 2022 ). The variations in the importance of deterministic and stochastic processes in the microbiota are likely habitat-dependent; therefore, investigating the assembly process in biological communities is important to explain the formation and maintenance mechanisms of biodiversity in the microbiota ( Zhou and Ning, 2017 ; Heys et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%